Comparative analysis of Islamic education: the North and South West Nigeria experience - Ashimi, Tijani Ahmad (Department of Islamic Studies, University of Abuja, 2019)
There is no doubt that education is a conscious and deliberate effort to create an atmosphere of learning and the learning process so that learner is actively developing his talent. This will enable spiritual strength, self-control, personality, noble character and the skill needed for his development and progress of society. Based on this fact, this article aims to explore the Islamic education in the north and south west Nigeria respectively. As a matter of fact, in the nineteenth century, when the Nigerian Muslims attempted to revive the process of education and knowledge in their societies, the Islamic education in both regions surfed a lots of set back ranging from organization, adoption, recognition and inferiority complex. However, in contemporary Nigeria, Islam and Christianity are predominant religions, as such, there is dual system of educations namely; Islamic education that is widespread in the Muslims dominating states and western secular education that is imposed by western colonial officer. Yet, this humble article will concentrate on Islamic education in the northern and south western part of the country (i.e. hausaland and yorubaland respectively). Indeed, the paper will adopt comparative approach to investigate the similarities and differences in operation of Islamic education at both regions. As far as Islamic education is concerned, and as far as western education is also important, this humble paper will finally suggest the integrative kind of education that if applied, will enhance the quality of Islamic education in the both regions in one hand, and that will help in building peaceful coexistence in another.